Analyse und Modellbildung von PEM-Brennstoffzellen mittels elektrochemischer Impedanzspektroskopie - Heinzmann, Marcel (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2024)
This work presents a physically motivated model for predicting the current/voltage behavior of PEM fuel cells. Extensive impedance measurements and DRT analyses were used to identify and quantify all loss processes. The developed model was successfully validated and provides insights into the internal processes of the fuel cell. It enables targeted optimization and shows great potential for increasing the performance of PEM fuel cells.